2016
DOI: 10.1017/cem.2016.351
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Emergency Department Sepsis Bundle and System Redesign: A Process Improvement Initiative

Abstract: Background: In 2008-2009, the Canadian Institute for Health Information reported over 30,000 cases of sepsis hospitalizations in Canada, an increase of almost 4,000 from 2005. Mortality rates from severe sepsis and septic shock continue to remain greater than 30% in Canada and are significantly higher than other critical conditions treated in the emergency department (ED). Our group formed a multidisciplinary sepsis committee, conducted an ED process of care analysis, and developed a quality improvement protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
3
9
0
11
Order By: Relevance
“…Additionally, we also implemented simulation training for ED nurses related to sepsis identification, care algorithms, standardized treatment protocols, and clinician roles and responsibilities. This QI supported the results of other studies incorporating a standardized process via education, interdisciplinary patient management, and visual tools, resulting in clinically significant results (14,15,41). Although numerous successful reports on the multidisciplinary approach have been published, limited publications on the human decision to activate sepsis response teams were found.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, we also implemented simulation training for ED nurses related to sepsis identification, care algorithms, standardized treatment protocols, and clinician roles and responsibilities. This QI supported the results of other studies incorporating a standardized process via education, interdisciplinary patient management, and visual tools, resulting in clinically significant results (14,15,41). Although numerous successful reports on the multidisciplinary approach have been published, limited publications on the human decision to activate sepsis response teams were found.…”
Section: Discussionsupporting
confidence: 82%
“…Sepsis order sets implemented using the Six-Source Influencer Model to create an atmosphere of teamwork to help counteract resistance to change, improved the process of care (14). A more recent study published in 2016 evaluated the effect of a QI sepsis management bundle on mortality and sepsis protocol compliance, determining that interdisciplinary ED sepsis bundles composed of triage flagging, registered nurse (RN) medical directives, education campaigns, and modified sepsis protocols improved early diagnosis and protocolized medical care resulting in improve care (15).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of patients who received fluids in this study is similar to previous retrospective studies [ 9 , 17 ]. The average time to first fluid administration was also similar compared to other studies [ 18 – 21 ] conducted in settings that use local protocols adapted from the Surviving Sepsis Campaign guidelines [ 22 ] similar to the Sepsis Pathway [ 11 ] used in the participating hospitals in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Unlike the negative results from recently published RCTs, most observational studies demonstrated that SSC bundle adherence was associated with a reduced mortality rate (9,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74), but without significantly increasing medical cost (75). Over a 7.5-year period running from 2005 till 2012, Levy et al found that compliance to the SSC bundle resulted in a 25% relative mortality risk reduction (76).…”
Section: Compliance With Surviving Sepsis Campaign (Ssc) Bundlementioning
confidence: 99%